Clinicopathological analysis of 18 cases of inflammatory myofibroblastic tumor in oral and maxillofacial region - Wei Li; Meng-chen Li; Zi-xuan Fan; Zi-chen Cao; Jie Yang; Xu-dong Yang; Xiao-feng Huang (BMC Oral Health)
Abstract Objective To analyze the clinicopathological features of inflammatory myofibroblastic tumor retrospectively and help maxillofacial surgeons to improve their recognition of its early diagnosis and proper treatment. Methods Data of 18 patients diagnosed with IMT in Nanjing Stomatological Hospital from November 2003 to July 2024 were collected. Their clinical, pathological, imaging features, treatment, and prognosis were analyzed. Results Main clinical manifestations were local masses, 8 cases were accompanied with malignant signs such as pain. No obvious systemic symptoms were reported. Bone destructions were seen in 3 cases. Pathological examination showed that 12 cases were Type II IMT and 6 cases were Type I IMT. 15 cases underwent surgical resections and were followed up for at least 1 years without recurrence. Conclusions The clinical symptoms and imaging manifestations of head and neck IMT are not specific. It is necessary to diagnose IMT by biopsy before operation. Wide local excision is the most reliable treatment.